FGF23-Klotho axis in CKD. Issue 1 (December 2016) - Takashi, Yuichi; Fukumoto, Seiji
Abstract Fibroblast growth factor 23 (FGF23) is a bone-derived hormone regulating phosphate and vitamin D metabolism. FGF23 works by binding to Klotho-FGF receptor (FGFR) complex. FGF23 reduces serum phosphate level by suppressing the expression of type 2a and 2c sodium-phosphate cotransporters in the renal proximal tubules. In addition, FGF23 suppresses intestinal phosphate absorption by reducing 1, 25-dihydroxyvitamin D (1, 25(OH)2 D) level. FGF23 also inhibits the production and secretion of parathyroid hormone. FGF23 starts to increase in the early phase of chronic kidney disease (CKD) and is considered to prevent the development of hyperphosphatemia. With the progression of CKD, the expression of Klotho decreases causing impaired actions of FGF23. It has been reported that FGF23 level is correlated with various adverse events including cardiovascular diseases especially in patients with CKD. It was also shown that FGF23 induces left ventricular hypertrophy by directly acting on cardiomyocytes in a Klotho-independent way. However, there still remain several unanswered questions concerning FGF23-Klotho axis. We hope that further studies elucidate unsolved problems and will be useful for more appropriate management of patients with CKD.